2016
DOI: 10.5539/jel.v5n2p233
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Science Teachers’ Beliefs on Teaching Science: The Case of Saudi Science Teachers

Abstract: The researcher aims to investigate Saudi science teachers' beliefs about learning and teaching issues. The sample consisted of 247 middle school teachers in Riyadh, Saudi Arabia. The study conducted in the academic school year 2014/2015, and utilized a questionnaire and an interview that included 10% of the sample. The questionnaire targeted the teachers' conceptions of learning and teaching issues and examined whether these conceptions fit the transmission, or discovery, of constructivist approaches. The inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 31 publications
0
5
0
3
Order By: Relevance
“…Estos cuestionamientos llevan pensar en nuevas prácticas en la escuela, seguidas de procesos de reflexión y conceptualización que pueden ser un camino factible para introducir nuevas concepciones en los procesos de enseñanza de las ciencias naturales. Alabdulkareem (2016) admitió que las prácticas docentes están profundamente influenciadas por la forma en que aprendieron ciencias y sostuvo que sus prácticas en el aula son avanzadas porque la educación ha experimentado enormes cambios en las últimas décadas. Sin embargo, es evidente por sus observaciones en el aula, que los docentes enseñan exactamente de la manera en que se les enseñó en sus procesos de formación.…”
Section: Las Concepciones Como Estructuras Del Saberunclassified
“…Estos cuestionamientos llevan pensar en nuevas prácticas en la escuela, seguidas de procesos de reflexión y conceptualización que pueden ser un camino factible para introducir nuevas concepciones en los procesos de enseñanza de las ciencias naturales. Alabdulkareem (2016) admitió que las prácticas docentes están profundamente influenciadas por la forma en que aprendieron ciencias y sostuvo que sus prácticas en el aula son avanzadas porque la educación ha experimentado enormes cambios en las últimas décadas. Sin embargo, es evidente por sus observaciones en el aula, que los docentes enseñan exactamente de la manera en que se les enseñó en sus procesos de formación.…”
Section: Las Concepciones Como Estructuras Del Saberunclassified
“…b) Students are found to be able to investigate and make explicit connections between what they learn in science class and what they learn outside of school in their local environment. c) This finding is very important in implementing the process of teaching and learning science and engineering as it is closely related to the rural environment of student life Alabdulkareem, 2016 The Impact of Science Teachers' Beliefs on Teaching Science: The Case of Saudi Science Teachers…”
Section: Cosee-ak Ocean Science Fairs: a Science Fair Model That Groumentioning
confidence: 99%
“…Teachers "understanding will impact teachers" pedagogy. Alabdulkareem (2016) finds that teachers' weakness in integrating science education in rural schools in Saudi is that teachers saw science as a separate issue and could not easily link it with cultural and historical issues.…”
Section: Teacher's Understandingmentioning
confidence: 99%
“…• Theme 1: Beliefs regarding their own self-efficacy • Theme 2: Beliefs regarding science teaching methods and strategies • Theme 3: Beliefs regarding science content knowledge This structure covers the components that were investigated by the above-mentioned existing studies but re-classifies them into three themes. For example, the components of instruction, teaching and teaching objectives (Alabdulkareem, 2016) was merged into Theme 2: Beliefs regarding science teaching methods and strategies. Similarly, the components of simple and real knowledge of science (Saylan et al, 2016) and the nature of science (Ibrahim, 2012;Al-Jazaeri, 2009) were merged into Theme 3: Beliefs regarding science content knowledge.…”
Section: Instrument and Proceduresmentioning
confidence: 99%
“…These PSTs may be unable to agree or disagree on these particular items because they lack teaching experience and need more training. Alabdulkareem (2016) has reported that science teachers' beliefs about key concepts were closely related to science teaching strategies such as instruction, teaching, teaching objectives, key teaching practices, and learners' error-correction strategies. All of these strategies are affected by the science teachers' beliefs about science teaching methods.…”
Section: Themementioning
confidence: 99%